The effect of fiber type and position on the transverse strength of an fiber reinforced composite (FRC) bridge - Pramudya Aditama; Erwan Sugiatno; Murti Indrastuti (Faculty of Dentistry, Universitas Gadjah Mada, 2020)
Fixed bridge made of porcelain fused to metal (PFM) is one of the widely used dentures. However, this type of denture is easily broken and cracked. As an alternative, a fixed bridge made of fiber-reinforced composite (FRC) is produced with more benefits since it is more efficient in terms of time and cost. The purpose of this research is to find out the effect of type and fiber position on the transverse strength of an FRC bridge. The experimentinvolved 35 rod of FRC with the dimensions of 25x2x2 mm3. Subjects were divided into seven groups, each of which containing five subjects. Group I, II, III was reinforced with glass fiber on compression side, neutral side, and tension side. Group IV, V, VI were reinforced with polyethylene (PE) fiber on compression side, neutral side, and tension side. Group VII was not reinforced with any fiber. Rods were tested for transverse strength with universaltesting machine and all data were analyzed with two way ANOVA at 95% confidence level. The results showed that type and position of fiber had a significant effect (p<0.05), while the interaction between type and position of fiber had no significant effect (p>0.05). Least significance different post hoc test showed significant difference (p<0.05) for all groups, except between compression and no fiber. The conclusion of this research was that addition of glass fibers on tension side in bridge FRC increased the transverse strength to be higher than that with PE fibers. Fiber placement on tension side might improve the transverse strength than that of the other side.